Analisis Pengelompokan Diagnosis Utama Berdasarkan ICD- 10 Di Rumah Sakit Kota Padang - Arifanil Hakim; Nila Mayasari (Iris Journal of Health Information Management, 2022)
Medical record is a description of patient identification, patient examination, diagnosis, treatment, actions and other services, whether carried out by doctors and dentists or other health workers in accordance with their competence. In conducting statistical analysis of health care can be done by using quantitative analysis which explains information in the form of numbers so that the results will be easier to use in decision making. Data collection was carried out at the hospital by recording the data of inpatients who went home, so that data were obtained as many as 554 patients with a total of 179 beds. Data processing is done using a computer with Microsoft Excel application program. Furthermore, the data were analyzed and the results of statistical processing of health care were presented in the form of tables and graphs of Barber Johnson. Most diagnoses were Bronchopneumonia with code J18.0 as many as 24 patients. The main diagnosis grouping based on defecation in ICD-10 the most diagnosis was CHAPTER XI (Disease of Digestive system) of 15.88% as many as 88 patients. The most procedures were Lithotomy Kidney with procedure code 55.01 totaling 14 patients. The main diagnosis according to the most DTD with code DTD 215 (urolithiasis) as many as 30 patients. Based on the RL4a report, the most age group was the age group of 25-44 years with 165 patients, based on female sex as many as 102 patients and male as many as 63 patients, while based on the disposition of life 551 patients, and 3 patients died. After processing the data, BOR was obtained as much as 35.66% or 36%, this BOR value was not efficient. BTR as much as 3.09 times for the efficient number of BTR is per year, then BTR cannot be calculated. IT is 6.44 days or 6 days, the obtained IT value is not efficient and ALOS is 3.57 days or 4 days, the ALOS value obtained is inefficient.